Ketahanan Kultivar Pisang Lokal Kalimantan Selatan terhadap Penyakit Bercak Sigatoka (Mycosphaerella sp.) - Mariana, Mariana; Rodinah, Rodinah; Budi, Ismed Setya (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2017)
Sigatoka of banana caused by Mycospherella sp. is an important disease, since it causes yield losses. Resistant variety is considered a promising approach for sigatoka disease management. This study was aimed to evaluate the resistance of local banana cultivars from South Kalimantan against sigatoka disease. The fungus was isolated from leaves of Kapas cultivar showing severe symptoms of sigatoka disease, onto potato dextrose agar medium. The isolate was then confirmed as Mycosphaerella sp. following Koch’s postulate. Level of resistance is determined based on symptoms development. Resistance of local banana cultivars can be differentiated into susceptible (‘Awak’, ‘Jaranang’, ‘Kapas’, ‘Mas’, and ‘Paikat’), medium resistant (‘Ambon’, ‘Kepok’, ‘Mas Bantan’, ‘Mauli’, and ‘Talas’), and resistant (‘Tarati’). In general, the symptom was visible 2 to 8 days after inoculation. The longer incubation period the more resistant response of banana varieties. Incubation period was negatively correlated to the disease intensity, but it is not correlated with stomatal density.